MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWERPOINT-WORDWALL UNTUK MEMUDAHKAN ANAK DALAM MENGHAFAL KOSAKATA BAHASA ARAB - Alifia, Annisa Rafa; Ilham, Mochammad Nafish; Syaifuddin, Tasya Syafira Rizkyyazahif; Sampurno, Tri Anggara Medhi; Asrori, Imam (Prosiding Konferensi Nasional Bahasa Arab, 2024)
The use of interactive media such as PowerPoint is effective for teaching Arabic to young children, as it facilitates understanding through visualization. However, since children enjoy learning through play, PowerPoint alone is less optimal due to its limited interactive elements. The solution is to combine PowerPoint, which provides structured material, with Wordwall, which offers game-like elements, creating a more enjoyable learning experience. This article will identify the effectiveness of combining PowerPoint and Wordwall as interactive learning media for young children. It employs a literature review method and finds that the combination of interactive PowerPoint and Wordwall creates a varied, effective, and enjoyable approach to teaching Arabic. PowerPoint offers clear structure in presenting material, while Wordwall adds interactive game elements that enhance children's motivation to learn.يعد استخدام الوسائط التفاعلية مثل برنامج PowerPoint فعالاً لتعلم اللغة العربية في مرحلة الطفولة المبكرة، لأنه يسهل الفهم من خلال التصور. ومع ذلك، نظرًا لأن الأطفال يحبون التعلم أثناء اللعب، فإن PowerPoint ليس مثاليًا لأنه يحتوي على عدد قليل من الألعاب. الحل هو الجمع بين PowerPoint، الذي يقدم مواد منظمة، وWordwall، الذي يوفر عناصر اللعبة، وبالتالي خلق تجربة تعليمية أكثر متعة. ستحدد هذه المقالة كيفية عمل مجموعة PowerPoint وWordwall كوسيلة تعليمية تفاعلية لمرحلة الطفولة المبكرة. تستخدم هذه المقالة طريقة دراسة الأدب. توصلت هذه المقالة إلى نتائج مفادها أن الجمع بين برنامجي PowerPoint وWordwall التفاعليين كوسيلة لتعلم اللغة العربية في مرحلة الطفولة المبكرة يخلق نهجًا متنوعًا وفعالًا وممتعًا. يوفر PowerPoint بنية واضحة في تقديم المواد، بينما يضيف Wordwall عناصر ألعاب تفاعلية تزيد من حماس الأطفال للتعلم.